X‐ray harmonics rejection on third‐generation synchrotron sources using compound refractive lenses. (12th March 2014) - Polikarpov, Maxim; Snigireva, Irina; Snigirev, Anatoly
<x xml:space="preserve">Abstract</x> A new method of harmonics rejection based on X‐ray refractive optics has been proposed. Taking into account the fact that the focal distance of the refractive lens is energy‐dependent, the use of an off‐axis illumination of the lens immediately leads to spatial separation of the energy spectrum by focusing the fundamental harmonic at the focal point and suppressing the unfocused high‐energy radiation with a screen absorber or slit. The experiment was performed at the ESRF ID06 beamline in the in‐line geometry using an X‐ray transfocator with compound refractive lenses. Using this technique the presence of the third harmonic has been reduced to 10−3. In total, our method enabled suppression of all higher‐order harmonics to five orders of magnitude using monochromator detuning. The method is well suited to third‐generation synchrotron radiation sources and is very promising for the future ultimate storage rings.